Analysis of the Usage of BKN E-Performance in Improving the Results And Teachers’ Work Behaviour of Religious Education At the Elementary School At Ministry of Religious Office of Medan City - Pandiangan, Pinta Omastri; Panjaitan, Binur; Sitio, Robert Juni Tua (the International Journal of Education, Theology, and Humanities, 2024)
Bureaucratic reform in every line of government agencies has changed the pattern of information disclosure through the digitalisation of government bureaucracy. Along with the demands of digitalisation and the issuance of Permen PanRB Number 6 of 2022, the Ministry of Religious Affairs of Medan City as a government agency must participate in the successful implementation of performance management through the BKN e-performance application. For this reason, the researcher formulated the problem 'how is the application of the e-performance application for religious education teachers at the primary school level at the Medan City Office of the Ministry of Religion and how the e-performance application can improve teacher behaviour and work results'. The purpose of the research is to describe and analyse the process of implementing the e-performance application by religious education teachers in improving work outcomes and work behaviour. The research method in this study uses qualitative research using Miles and Huberman data analysis. The research subjects were religious education teachers at the primary school level at the Medan City Ministry of Religious Affairs Office, with 10 (ten) main informants and 3 (three) key informants as verifiers, namely 1 (one) staffing section and 2 (two) section heads. The results of the study generally show that the implementation of the e-performance application has been carried out but not in accordance with the stages of performance management and the application of the BKN e-performance application can improve the work results and work behaviour of teachers, this is based on the results of interviews conducted on the main informants and key informants. On the other hand, the implementation of the e-performance application is not accompanied by socialisation and training, limited IT skills of teachers, the absence of performance dialogue to reach an agreement in determining RHK, setting expectations and assessment standards for work results and work behaviour. In addition, the predicate assessment does not show any differences in work results between teachers and cannot be used as a reference for teacher performance progress. Referring to the results of the study, the researcher recommends that teachers be more proactive in seeking information and learning independently. The researcher also recommends that the Ministry of Religious Affairs of Medan City continue to provide e-performance training, form a special performance team, build performance dialogue, quantitative/numerical form of assessment of work results and behaviour, and include curves/diagrams of improvement in performance results and behaviour in the application as a measure of performance success.